Cardiovascular risk and bone loss in men undergoing androgen deprivation therapy for non‐metastatic prostate cancer: implementation of standardized management guidelines. (20th May 2013) - Cheung, A. S.; Pattison, D.; Bretherton, I.; Hoermann, R.; Lim Joon, D.; Ho, E.; Jenkins, T.; Hamilton, E. J.; Bate, K.; Chan, I.; Zajac, J. D.; Grossmann, M.
Summary Our objective was to evaluate the effectiveness of implementing standardized guidelines to mitigate metabolic and bone side effects of androgen deprivation therapy (ADT) in men with non‐metastatic prostate cancer. We conducted a 2‐year prospective cohort study at a tertiary referral teaching hospital. Overall, 236 men (mean age 69.8 ± 7.1) commencing ADT for non‐metastatic prostate cancer attended a baseline clinic visit between 2007 and 2011, and 153 men were eligible for follow‐up after 2 years of continuous ADT. Of these, 113 men had data available for analysis at 2 years. At baseline, 87% of the men were overweight or obese, 61% had hypertension, 56% had hypercholesterolaemia, 27% prior cardiovascular disease, 11% osteoporosis and 40% osteopaenia. After 2 years of ADT, there was an increase in waist circumference (+2.8 ± 6.3 cm, p = 0.002), and, in men without diabetes, in HbA1c (+0.13 ± 0.34%, p = 0.019). Despite this, due to treatment, there were significant reductions in total cholesterol (−0.35 ± 1.00 mmol/L, p < 0.001), and blood pressure (systolic −7.6 ± 19.3 mmHg; diastolic −4.7 ± 11.6 mmHg, p < 0.001). After 2 years, men not receiving anti‐resorptive therapy experienced a significant decline in lumbar spine (−0.042 ± 0.134 g/cm2, p = 0.012) and total hip bone mineral density (BMD) (−0.026 ± 0.036 g/cm2, p < 0.001), whereas bisphosphonate treatment maintained stable BMD. Prevalence of anaemia increased from 13.8 to 32.5%. Older age independently predicted a greater drop in haemoglobin (p = 0.005). We conclude that a structured approach to assess and treat men undergoing ADT effectively improves cardiovascular risk factors and prevents bone decay. Larger studies are needed to determine effects on cardiovascular outcomes, fracture prevention and survival.